Outsourcing IT jako jedna z form ograniczania kosztów - Kin-Dittmann, Irena (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
We use outsourcing in many domains of economic activity. This is one of the ideas that lead to better fitting the organization into functioning on the global market. In Poland mainly big and medium enterprises from industry and financial sector are taking advantages from outsourcing IT. Outsourcing of IT makes firms structures leaner and enables cost reduction. Diversity of forms and scope of outsourcing in Poland grows while its development
Keywords: outsourcing; IT; sektor usług